Superovulatory response and embryo quality of Holstein heifers treated with one or two injections of somatotropin - González Maldonado, Juan; Rangel Santos, Raymundo; Rodríguez de Lara, Raymundo (Revista Colombiana de Ciencias Pecuarias, 2015)
Background: recombinant bovine somatotropin (rbST) is used in bovine embryo donors to improve superovulatory response and embryo quality. Objective: this study evaluated the effect of applying one versus two injections of 500 mg of rbST to donor Holstein heifers on estrus incidence (IE), diameter of the largest preovulatory follicle (dLPF), superovulation response (SR), embryo yield, and pregnancy rate in recipient Holstein cows (PRR). Methods: two superstimulation programs were conducted. Heifers were assigned to one of two treatments: 1) rbST-I, n = 5: heifers received one injection of rbST on day 0 (day of CIDR (controlled internal drug release) removal); 2) rbST-II, n = 5: heifers received the first rbST injection on day -8 and the second one on day 0. Thirty-eight cows were used as recipients and were assigned to receive one embryo from one of the two treatments. Results: there was no effect of treatment (p > 0.05) on PRR, dLPF, IE, and SR. The number of oocytes increased (p < 0.05) in the rbST-I treatment (1.3 ± 0.4 vs 0.2 ± 0.2), but there was no difference in the number (p > 0.05) of degenerated (1.0 ± 0.5 vs 4.5 ± 3.0) or transferable (1.0 ± 0.5 vs 1.4 ± 0.7) embryos between heifers in the rbST-I and rbST-II treatments, respectively. Moreover, no oocytes or embryos were recovered from 36.8% of donor heifers in either treatment. Conclusion: the application of 500 mg of rbST on days -8 and 0 of the follicular wave synchronization program did not increase the superovulatory response but significantly reduced the number of oocytes recovered from superovulated Holstein heifers.